The return on human (STEM) capital in Belgium - Gert Bijnens; Emmanuel Dhyne (National Bank of Belgium, 2021)
Whilst overall productivity growth is stalling, firms at the frontier are still able to capture the benefits of the newest technologies and business practices. This paper uses linked employer-employee data covering all Belgian firms over a period of almost 20 years and investigates the differences in human capital between highly productive firms and less productive firms. We find a clear positive correlation between the share of high-skilled and STEM workers in a firm's workforce and its productivity. We obtain elasticities of 0.20 to 0.70 for a firm's productivity as a function of the share of high-skilled workers. For STEM (science, technology, engineering, mathematics) workers, of all skill levels, we find elasticities of 0.20 to 0.45. More importantly, the elasticity of STEM workers is increasing over time, whereas the elasticity of high-skilled workers is decreasing. This is possibly linked with the increasing number of tertiary education graduates and at the same time increased difficulties in filling STEM-related vacancies. Specifically, for high-skilled STEM workers in the manufacturing sector, the productivity gain can be as much as 4 times higher than the gain from hiring additional high-skilled non-STEM workers. To ensure that government efforts to increase the adoption of the latest technologies and business practices within firms lead to sustainable productivity gains, such actions should be accompanied by measures to increase the supply and mobility of human (STEM) capital. Without a proper supply of skills, firms will not be able to reap the full benefits of the digital revolution.
Keywords: E24; I26; J24; 330; human capital; skills; education; productivity; linked employer-employee data